(untitled) (Research, Society and Development, 2020)
Experimental activities represent an indisputable resource in the teaching - learning process. For undergraduate students these practices become more efficient when treated in a contextualized manner. Physical methods of analysis are simple, low cost and fast alternatives in verifying the authenticity of essential oils with high commercial value, besides offering experimental didactics that facilitate the learning of students in chemistry and related areas. Among the physical parameters are density, refractive index and optical rotation, which regulate the commercialization of herbal medicines in Brazil. This study aims to provide alternatives of experimental activity in the teaching of chemistry aimed at practical application related to regulation in the marketing of essential oil with high added value and scientific production in the area. The essential oils were obtained by hydrodestillation. Density, refractive index and specific rotation were measured in specific devices. The lamp essential oil obtained higher specific rotation (-58.75° to -59.25°). The refraction index was higher for the oil stick (1.501560 ± 0.000000 nD). The density was higher for the red marangaba essential oil (0.98 ±0.015 g/mL). Changes in the chemical composition of essential oils present significant changes in their physical properties, these can be easily identified with the help of easily accessible and handling devices, ensuring efficiency of their biological properties. The students can develop professional skills to identify these characteristics, a possibility that represents motivation in the teaching-learning process.